Ritual for the slaughter of a bull - Allpanchis, Revista (1971)
On December 8, Cotabambas celebrates its feast, the Immaculate Conception of Mary. The slaughter of the bull takes place on December 7, the day before the festival, in the house of the cargoyoq. The bull's meat will be consumed by the entire town.